DUALISME KEDUDUKAN DAN TANGGUNG JAWAB NOTARIS DALAM TATANAN SISTEM HUKUM NASIONAL - Isis Ikhwansyah; Indra Prayitno (Asy-Syari'ah, 2019)
Abstract: Government policies related to notary institutions from the beginning of their emergence until now, it has not been able to provide certainty related to the independence of the Notary Position in the order of the National legal system. Is it purely as a public official like a state official, or is the legal profession, and or is a Public Official combined with a legal profession position because it influences his responsibilities. This study aims to find out how the position and responsibilities of a notary in the current national legal system, this research method uses a juridical normative approach method that is analyzed descriptively analytically on the basis of data that is processed in a juridical way qualitatively, logically and systematically. From the results of the study note that the Notary has a position as a "Public Official" based on “the provisions of Article 1868 of the Civil Code”, UUJN, and other relevant laws. Notary public is also said to be a "professional position" because it has the skills and is done continuously to serve the interests of the community in the sphere of civil (Private). The notary's responsibility as a "Public Official" arises when the notary carries out the authority regulated under the UUJN and is responsible for carrying out his position to the client as well as to the government that has appointed him. The professional responsibility of a notary public arises when applying his skills in serving the community and being responsible to himself and his professional organization.Abstrak: Berbagai kebijakan pemerintah sehubungan dengan lembaga kenotariatan dari awal kemunculannya hingga saat ini, belum dapat memberikan kepastian terkait dengan independensi kedudukan notaris dalam tatanan sistem hukum nasional. Apakah murni sebagai pejabat umum layaknya pejabat negara, ataukah profesi hukum, dan ataukah pejabat umum yang dipadukan dengan jabatan profesi hukum karena hal tersebut berpengaruh terhadap tanggung jawabnya. Penelitian ini bertujuan untuk menemukan kedudukan serta tanggung jawab notaris dalam tatanan sistem hukum nasional saat ini, metode penelitian yang digunakan adalah metode pendekatan yang dilakukan secara yuridis normatif  yang dianalisis secara deskriptif analitis atas dasar data yang diolah secara yuridis kualitatif, logis dan sistematis. Dari hasil penelitian diketahui bahwa notaris mempunyai kedudukan sebagai “pejabat umum” didasarkan pada ketentuan “pasal 1868 kuhperdata”, uujn, serta perundang-undangan terkait lainnya. Notaris juga dikatakan sebagai “jabatan profesi” karena memiliki keterampilan dan dilakukan secara terus menerus untuk melayani kepentingan masyarakat dalam lingkup keperdataan (privat). Tanggung jawab notaris sebagai “pejabat umum” muncul ketika notaris melaksanakan kewenangan yang diatur berdasarkan uujn dan bertanggungjawab terhadap pelaksanaan jabatannya kepada klien serta kepada pemerintah yang telah mengangkatnya. Tanggung jawab professional dari seorang notaris muncul ketika menerapkan keterampilannya dalam melakukan pelayanan pada masyarakat dan bertanggungjawab kepada diri sendiri serta organisasi profesinya.